Moldura analítica para priorizar a automação de processos de trabalho na UFSCar - Danini, Thiago Sentanin (2018)
Brazilian public organizations face daily difficulties to adapt to the demands of society, following the evolution of information technology concerning to business management models. In this sense are the Federal Institutions of Higher Education, which seeks to meet the society demand for affordable and quality higher education, as well as contribute to the scientific and technological development of Brazil, have seen their organizational processes reach a high complexity and diversity degree. However, the practices and methods adopted to execute these processes are often obsolete and not automated, which may compromise the achievement of their institutional project. Furthermore, resources scarcity made the decision-making procedure a key factor in organizational management and in this sense the identification and prioritization of which processes should be worked first is important. The overall aim of this research, based on the business process management approach, was to develop and apply an analytical molding (matrix) of prioritization as a way of evaluating and set priorities how much the of work process automation initiatives in UFSCar. The action-research was used as a method and the case-unit was the Informatic General Secretary of the Federal University of São Carlos. The results included both the development of an analytical molding (matrix) of prioritization to analyze the work processes and to define priorities regarding the systems development as well as their application in the case-unit, which involved four steps: 1] Diagnosis of the current situation; 2] Development of the matrix; 3] Application of the matrix; 4] Analysis of results. Concludes based of the theoretical discussion and analysis of the results that, through the proposed analytical molding, it was possible not only to know and analyze the processes considering their characteristics and information, but also to subsidize the choice of which process should be automated first. Furthermore, the use of the Prioritization Matrix provides transparency and credibility toward choice through establishing criteria.